The Concept of Islamization of Knowledge According to Hamid Fahmy Zarkasyi - Ismail Ismail; Junaidi Arsyad; Yusnaili Budianti (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study critically examines the integration of the Islamic worldview into modern educational systems through the Islamization of knowledge framework, focusing on Hamid Fahmy Zarkasyi's epistemological contributions. Employing qualitative library research with a character study approach, this research analyses primary sources, including Zarkasyi's scholarly works, alongside secondary literature from al-Attas and al-Faruqi. Findings reveal that contemporary Islamic education suffers from an epistemological crisis rooted in the uncritical adoption of secular Western paradigms that contradict tawhidic foundations. Zarkasyi proposes a three-stage framework: epistemic identification of secular assumptions, critical deconstruction of contradictory presuppositions, and reconstruction upon tawhid, prophethood, and Islamic ethics. This research demonstrates that Islamization transcends theoretical discourse, offering concrete solutions to the knowledge-value dichotomy plaguing Muslim education. The study concludes that authentic Islamic educational reform requires dismantling and reconstructing knowledge paradigms themselves, not merely administrative or methodological adjustments. Implications include curriculum redesign integrating Islamic worldview, establishment of interdisciplinary research centres, and teacher training in Islamic epistemology to produce graduates with balanced spiritual integrity and intellectual competence